Antenatal Magnesium Sulfate, Necrotizing Enterocolitis, and Death among Neonates < 28 Weeks Gestation - Manijeh Kamyar; Erin A. S. Clark; Bradley A. Yoder; Michael W. Varner; Tracy A. Manuck (American Journal of Perinatology Reports, 2016)
Abstract